Accuracy of Intra-oral Scans Compared to Conventional Impression in Vitro. Issue 3 (September 2019) - Haddadi, Yasser; Bahrami, Golnosh; Isidor, Flemming
AIM: The purpose of the present study was to assess the accuracy of intra-oral scans and conventional impression measured at various points on a single tooth preparation. Methods: Ten conventional silicone impressions, and ten intra oral-scans using eight different digital intra oral digital scanners were taken of a prepared master tooth. The conventional impressions were directly digitised using a laboratory scanner. Each scan/impression was superimposed on a high-accuracy digital model of the prepared master tooth. For each superimposition, the deviation from the prepared master tooth was measured at six points on four two-dimensional cross-sections. Data was analysed using two-way analysis of variance (ANOVA). Results: Most intra oral scanners had lower accuracy at the preparation margin compared to smooth surfaces. When only conventional impression and the latest intra oral scanners of various manufacturers are considered, the mean discrepancy at the preparation margin was 50μm (SD 16) for conventional impression, 15μm (SD 4) for Trios 3, 26μm (SD 4) for LAVA TDS, 29μm (SD 7) for CEREC Omnicam, 30μm (SD 6) for CS 3600 and 64μm (SD 7) for GC Aadva. The increased accuracy of Trios 3 was statistically significant (p<0.05). Conclusions: At the preparation margin, Trios 3 performed significantly better than conventional impression and the other intra oral scanners. LAVA TDS, CEREC Omnicam and CS3600 showed similar accuracy at the margin, yet better than conventional impression and GC Aadva.